Vegetation Diversity and Conservation Status in the Green Space of the Faculty of Medicine, University of Indonesia - Deanova Frestiana Br. Pelawi; Tazkiyatul Syahidah; Harto; Rizmoon Nurul Zulkarnaen (Talenta Publisher, 2026)
Green space enhances environmental quality and maintains ecosystem balance in urban areas. This study examines the vegetation in the green space at the Salemba and Cikini campuses and assesses species diversity and conservation status based on the IUCN Red List. A total of 514 individual plants, representing 107 species from 38 families, were recorded, with dominant species including Monoon longifolium, Terminalia neotaliala, and Thyrsostachys siamensis. Species diversity analysis revealed a Shannon-Wiener index (H') of 4.07, Simpson's index (D) of 0.97, and evenness (E) of 0.87, indicating high diversity and a well-distributed plant community. Among the species identified, 61 individuals from 6 species were classified as threatened, including 2 Critically Endangered, 24 Endangered, and 35 Vulnerable individuals. These findings highlight the urgency for enhanced conservation efforts to prevent the extinction of these species. Sustainable management strategies should integrate both ecological and social factors, emphasizing biodiversity-focused interventions, public participation, and strategic conservation planning. This study underscores the need for comprehensive vegetation management and increased public awareness to preserve urban biodiversity and support broader sustainability initiatives.